Autophagy and Apoptosis Interact to Modulate T-2 Toxin-Induced Toxicity in Liver Cells - Jing Wu; Yu Zhou; Zhihang Yuan; Jine Yi; Jingshu Chen; Naidong Wang; Yanan Tian (Toxins, 2019)
T-2 toxin is a mycotoxin generated by Fusarium species which has been shown to be highly toxic to human and animals. T-2 toxin induces apoptosis in various tissues/organs. Apoptosis and autophagy are two closely interconnected processes, which are important for maintaining physiological homeostasis as well as pathogenesis. Here, for the first time, we demonstrated that T-2 toxins induce autophagy in human liver cells (L02). We demonstrated that T-2 toxin induce acidic vesicular organelles formation, concomitant with the alterations in p62/SQSTM1 and LC3-phosphatidylethanolamine conjugate (LC3-II) and the enhancement of the autophagic flux. Using mRFP-GFP-LC3 by lentiviral transduction, we showed T-2 toxin-mediated lysosomal fusion and the formation of autophagosomes in L02 cells. The formation of autophagosomes was further confirmed by transmission electron microcopy. While T-2 toxin induced both autophagy and apoptosis, autophagy appears to be a leading event in the response to T-2 toxin treatment, reflecting its protective role in cells against cellular damage. Activating autophagy by rapamycin (RAPA) inhibited apoptosis, while suppressing autophagy by chloroquine greatly enhanced the T-2 toxin-induced apoptosis, suggesting the crosstalk between autophagy and apoptosis. Taken together, these results indicate that autophagy plays a role in protecting cells from T-2 toxin-induced apoptosis suggesting that autophagy may be manipulated for the alleviation of toxic responses induced by T-2 toxin.